Marketing legal services on the Internet - Alicja Mikołajczyk (Contemporary Economy, 2014)
This article describes accessible means of marketing legal services under restrictive regulations in the Polish market. As attorneys-at-law and legal advisers face significant legal and ethical limitations in their market communication, they are forced to seek alternative tools of promoting their services and reaching potential clients. Electronic media turned out to be an effective and convenient channel in marketing legal services, often prevailing offline marketing communication. The article presents legal restrictions in the market, with emphasis to fundamental barriers that prevent implementation of traditional marketing tools and techniques broadly available in market communication. The second part presents selected tools of online marketing applicable in promotion of legal services, examplified with their use in practice.